Improved therapeutic management of women with endometriosis - Татарчук, Т. Ф; Захаренко, Н. Ф.; Маноляк, І. П.; Ковбасій, В. П. (REPRODUCTIVE ENDOCRINOLOGY, 2014)
It was developed and tested a complex drug therapy of women with endometriosis. Within 6 months of the study’s authors are actively watching the 80 women with adenomyosis, which were divided into two groups. The first group of women (n = 42) administered progestin therapy for 6 months – Vissane (dienogest 2 mg). The second group included 38 patients treated with combined therapy: Vissane (dienogest 2 mg) daily for 6 months, Adaptol (mebicar 500 mg) twice a day and Noophen (phenibutum 250 mg) twice a day for three months. The results showed a slightly higher clinical efficacy of progestogen therapy (Visan) in combination with non-hormonal drugs (Adptol and Noophen).